Going‐Concern Status, Earnings Persistence, and Informativeness of Earnings* - SUBRAMANYAM, K.R.; WILD, JOHN J. (Contemporary Accounting Research, 1996)
Abstract. Valuation theory recognizes that the relation between earnings innovations and changes in security valuation is increasing in the persistence of the earnings innovations. Analyses in this article reveal that the present value of revisions in expected future benefits is a function of the length of revision horizon, suggesting that earnings persistence is determined, in part, by an entity's going‐concern status. These analyses predict an inverse relation between earnings informativeness and an entity's probability of termination. Drawing on a sample of quarterly earnings and returns data from more than 1,500 distinct firms for the period 1981–1990, a statistically significant inverse relation is documented between an entity's probability of termination and the informativeness of earnings—the latter measured as the coefficient from a regression of returns on earnings. Further empirical analyses reveal that this result is a pervasive economic phenomenon not attributable to extreme conditions or other prevailing explanations of earnings informativeness. This inference is robust to variations in research design, including measurement of earnings informativeness and of termination probability and alternative specifications of the relation between returns and earnings. Consequently, the evidence in this article is consistent with a fundamental role for an entity's going‐concern status in determining the usefulness of earnings. Résumé. La théorie de l'évaluation reconnaît le fait que la relation entre les nouvelles informations relatives au bénéfice net et les changements dans l'évaluation des titres s'intensifie lorsque persistent lesdites informations. Les analyses réalisées par les auteurs révèlent que la valeur actualisée des rajustements dans les gains futurs espérés dépend de l'horizon du rajustement, ce qui donne à penser que la persistance du bénéfice net est en partie fonction de la continuité de l'exploitation de l'entreprise. Selon ces analyses, le potentiel informatif du bénéfice net devrait être en relation inverse avec la probabilité de fermeture de l'entité. En s'appuyant sur un échantillon de données trimestrielles relatives au bénéfice net et au rendement recueillies auprès de plus de 1500 entreprises distinctes pour la période 1981–1990, les auteurs observent une relation inverse statistiquement significative entre la probabilité de fermeture d'une entité et le potentiel informatif du bénéfice—ce dernier étant mesuré sous forme de coefficient, au moyen d'une régression des rendements sur les bénéfices. D'autres analyses empiriques révèlent que cette conclusion est un phénomène économique répandu qui n'est pas attribuable à des conditions extrêmes ou à d'autres explications prédominantes du potentiel informatif du bénéfice net. Cette inference résiste aux variations dans le plan de recherche, y compris la mesure du potentiel informatif du bénéfice net et de la probabilité de fermeture, et les autres caractéristiques possibles de la relation entre le rendement et le bénéfice. Les résultats obtenus confirment donc que la continuité de l'exploitation joue un rôle fondamental dans la détermination de l'utilité du bénéfice net.